Inherited pulmonary surfactant metabolism disorders in Argentina: Differences between patients with SFTPC and ABCA3 variants. Issue 2 (11th November 2022) - Balinotti, Juan E.; Mallie, Camila; Maffey, Alberto; Colom, Alejandro; Epaud, Ralph; de Becdelievre, Alix; Fanen, Pascale; Delestrain, Céline; Medín, Martín; Teper, Alejandro
Abstract: Background: Patients with inherited pulmonary surfactant metabolism disorders have a wide range of clinical outcomes and imaging findings. Response to current anti‐inflammatory therapies has been variable and efficacy is unclear. Objective: To describe and compare genetic, clinical, histological, and computed tomography (CT) outcomes in a cohort of patients with variants in the genes encoding surfactant protein C (SP‐C ) or adenosine triphosphate‐binding cassette transporter A3 (ABCA3) in Argentina. Methods: Observational cohort retrospective study. Patients carrying variants in genes encoding SP‐C and ABCA3 proteins were included. Results: Fourteen patients met the inclusion criteria: SFTPC n  = 6, ABCA3 n  = 8 (seven were heterozygous and one compound heterozygous). Neonatal respiratory distress was more frequent and severe in neonates with variants in the ABCA3 gene. The onset of the disease occurred in infancy before the age of 20 months in all cases. Patients with ABCA3 pathogenic variants had a severe clinical course, while long‐term outcomes were more favorable in individuals with SFTPC variants. Initial CT findings were ground glass opacities and intraparenchymal cysts in both groups. Over time, signs of lung fibrosis were present in 57% of patients with ABCA3 variants and in 33% of the SFTPC group. The efficacy of anti‐inflammatory interventions appears to be poor, especially for patients with ABCA3 pathogenic variants. Conclusions: Clinical, histological, and radiological features are similar in patients with SFTPC and ABCA3 variants; however, the latter have more severe clinical course. Current anti‐inflammatory regimens do not appear to stop the progression of the disease.